Morphological study on particulate matter of Kathmandu valley - Rauniyaar, Jyoti; Aryal, Girja Mani; Neupane, Bhanu Bhakta (BIBECHANA, 2018)
Air borne particulate matter (PM) depending on size, shape, concentration, and chemical composition can cause multitude of health issues. In this study, we report the morphological study of dust samples obtained from twenty different locations of Kathmandu valley by imaging the sample directly by a bright field optical microscope. We find that the average size of particles in all the samples examined below 10 micrometer. Individual examination of particles revealed that significant number of particles asymmetric. The observation of asymmetric particles having aspect ratio as high as 20 may suggest that asbestiform particles exist in all the dust samples examined.   BIBECHANA 16 (2019) 41-46